One-dimensional confinement of a nanosized metal organic framework in carbon nanofibers for improved gas adsorption - Pachfule, Pradip; Balan, Beena K.; Kurungot, Sreekumar; Banerjee, Rahul (Chemical Communications, 2012)
The loading of a Zn-terephthalate based MOF in the inner cavity as well as on the outer walls of a hollow carbon nanofiber (CNF) creates MOF@CNF hybrids. This hybrid ``MOF@CNF'' displayed improved thermal stability as well as gas adsorption compared to the individual counterparts.